Nanocomposites obtained from various acrylate resins with DPGDA reactive diluent filled with fumed silica particles produced by using a DLP/LCD-type 3D printer - Çakır, Mustafa; Akın, Emre (İdris Karagöz, 2024)
The present study presents various acrylate resin systems formulated with dipropylene glycol diacrylate (DPGDA) reactive diluent such as silicon acrylate (SiA), urethane acrylate (UA), and polyester acrylate (PEA) and their nanocomposites prepared by filling hydrophilic and amorphous fumed silica particles (FS) in different proportions produced by DLP (Digital Light Processing) and LCD (Liquid Crystal Display) (DLP/LCD) type 3D printers. The increase in the fumed silica content resulted in an increase in the ultimate tensile strength, the Young's modulus, the Izod impact strength, and the hardness values up to a certain value for each acrylate resin system. The PEA-DPGDA-2%FS nanocomposite showed an increase of 20.6% and 47.2% in the ultimate tensile strength and the Izod impact strength, respectively. A substantial increase in Izod impact strength of 61.7% was achieved with UA-DPGDA-1%FS. PEA-DPGDA and UA-DPGDA showed much higher mechanical properties than SiA-DPGDA. However, tensile strength, Young's modulus, and Izod impact strength of fumed silica-filled SiA-DPGDA samples showed substantial increases of 90%, 74.4%, and 60.8%, respectively.

Bu çalışmada, DPGDA reaktif seyreltici ile formüle edilmiş silikon akrilat (SiA), uretan akrilat (UA) ve poliester akrilat (PEA) gibi çeşitli akrilat reçine sistemleri ve bunların farklı oranlarda hidrofilik ve amorf yapıya sahip dumanlı silika parçacıkları ile doldurularak DLP/LCD tipi 3B yazıcı tarafından üretilen nanokompozitleri hazırlanmıştır. Dumanlı silika içeriğindeki artış, her bir akrilat bazlı reçine sistemi için maksimum çekme dayanımı, Young modülü, Izod darbe dayanımı ve sertlik değerlerinde belirli bir noktaya kadar artışa neden olmuştur. PEA-DPGDA-%2FS nanokompoziti, maksimum çekme ve Izod darbe dayanımında sırasıyla %20,6 ve %47,2'lik bir artış göstermiştir. UA-DPGDA-1%FS ile Izod darbe dayanımında %61,7 oranında önemli bir artış elde edilmiştir. PEA-DPGDA ve UA-DPGDA, SiA-DPGDA numunesinden çok daha yüksek mekanik özellikler göstermiştir. Bununla birlikte, dumanlı silika dolgulu SiA-DPGDA numunelerinin maksimum çekme dayanımı, Young modülü ve Izod darbe dayanımı sırasıyla %90, %74,4 ve %60,8 oranında önemli artışlar göstermiştir.
DLP/LCD tipi 3D yazıcı kullanılarak dumanlı silika parçacıkları ile doldurulmuş DPGDA reaktif seyrelticili çeşitli akrilat reçinelerinden üretilen nanokompozitler
Keywords: Polymer Physics; Polimer Fiziği [EN] Polymer Technologies; Polimer Teknolojisi [EN] Polymers and Plastics; Polimerler ve Plastikler